The Utilization of Extracting Machine Technology at the Red Ginger Instant Business in Kwala Bekala Urban Village - Sinamo, Karina Nola; Hutabarat, Nauas Domu Marihot Romauli; Karo-karo, Terip; Ginting, Sentosa (Talenta Publisher, 2023)
Partner started a red ginger instant powder business during the covid-19 pandemic. Partner knowed the benefits of red ginger in increasing the body's immune power to prevent infection with the Corona virus. The service team found that partner produced red ginger instant powder manually using simple equipment. One of them was the process of extracting red ginger and other spices by squeezing the finely ground red ginger and other spices using a cloth. This made the production process ineffective and the amount of extraction results was not maximized. The manual extortion process using the cloth taked a long time and a large amount of human labor so that partner was constrained in making large quantities so that some orders are delayed. Therefore, partners had difficulty in carrying out the extraction process of red ginger, especially in large quantities. The solution offered by the service team was to utilize extracting machines according to partner needs and provide training in using red ginger extracting machines to partners. The result was that the partner became skilled at using the extracting machine in producing instant red ginger and trying to improve their business.